Seeing your own touched hands in a mirror modulates cross-modal interactions. - Maravita, A; Spence, C; Sergent, C; Driver, J (2002)
In mirror reflections, visual stimuli in near peripersonal space (e.g., an object in the hand) can project the retinal image of far, extrapersonal stimuli "beyond" the mirror. We studied the interaction of such visual reflections with tactile stimuli in a cross-modal congruency task. We found that visual distractors produce stronger interference on tactile judgments when placed close to the stimulated hand, but observed indirectly as distant mirror reflections, than when directly observed in equivalently distant far space, even when in contact with a dummy hand or someone else's hand in the far location. The stronger visual-tactile interference for the mirror condition implies that near stimuli seen as distant reflections in a mirror view of one's own hands can activate neural networks coding peripersonal space, because these visual stimuli are coded as having a true source near to the body.